YOUDEN'S TEST FOR CHROMATOGRAPHIC DETERMINATION OF ENALAPRIL IN PHARMACEUTICALS - Logoyda, L. S. (International Journal of Medicine and Medical Research, 2020)
Background. Robustness tests were firstly introduced for avoiding problems in interlaboratory studies and identifying the factors potentially responsible. A robustness test performing in late validation procedure involves the possibility that when the method is established not robust, it should be redeveloped and optimized. At this stage much effort has been made and money spent for optimization and validation, and therefore avoiding this would be great. Objective. The aim of the study was to consider the robustness of HPLC determination of enalapril (in tablets) by the Youden’s test. Methods. Youden’s test was chosen as an efficient method to assess the robustness among all analytical methods that is by means of an experiment design, which involved seven analytical parameters combined in eight tests. In previous studies, we evaluated the chromatographic method robustness to quantify enalapril (in tablets) by Youden’s test. Results. According to the Youden’s test criteria, HPLC method proved to be greatly robust regarding the enalapril content in introduction of variation of seven analytic parameters. The lowest variation in enalapril content was 0.91 %, when Grace Platinumр C8 EPS column (4.6 mm i.d. X 250 mm, 5 μm) was used. A holistic approach concerning simultaneous innovations in particle technology and instrument design was endeavored for the first time to meet and tackle the analytical laboratory issues. This was aimed at promoting success of analytical scientists as well as profitability and productiveness of business. Conclusion. The Youden’s test has been proved to be an efficient and useful tool for evaluation of robustness of enalapril HPLC assay.